The Effect of Kratom Leaf Alkaloid Extract on Blood Glucose Levels Using an In Vivo Method - Dewi, Bastiana; Kamilla, Laila; Sutriswanto, Sutriswanto; Tumpuk, Sri; Triana, Linda (Jurnal Laboratorium Khatulistiwa, 2025)
Kratom contains alkaloids, flavonoids, saponins, and tannins, which have traditionally been used to boost energy and treat various health conditions, including diabetes. This study aims to analyze the effect of kratom leaf alkaloid extract on blood glucose levels in vivo using a quasi-experimental design. The subjects were 27 male Swiss Webster mice (Mus musculus), divided into three treatment groups receiving kratom leaf alkaloid extract at doses of 0.147 mg/20gBW, 0.294 mg/20gBW, and 0.588 mg/20gBW. The alkaloid extract was obtained through fractionation. Each treatment group was replicated nine times using purposive sampling. An oral glucose tolerance test was conducted to measure blood glucose levels. The Simple Linear Regression test results showed a p-value of 0.000 (p < 0.05), indicating a significant effect of kratom leaf alkaloid extract on blood glucose levels in vivo.